Pemetaan Psikologi Olahraga, Kesehatan Mental dan Performa Atlet: Scopus Tren Global 2014-2024 - Akhmad, Noor; Badaru, Benny; Hasanuddin, M. Imran; Isyani, Isyani (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This study aims to analyze global trends in sports psychology, mental health, and athlete performance during the 2014-2024 period. A bibliometric approach was employed, analyzing 324 documents sourced from Scopus-indexed databases. The dataset comprised English-language articles with final publication status. Data processing utilized OpenRefine to remove duplicates, standardize formatting, and filter irrelevant entries, ensuring high-quality data. Analytical techniques included VOSviewer and Biblioshiny to map publication trends, keyword distributions, and thematic relationships. Results revealed an annual publication growth rate of 37.41 percent, an average document age of 3.17 years, and a mean of 13.36 citations per document. Internationalcollaborations accounted for 32.1 percent of the publications, with the United States contributing 70 documents, followed by the United Kingdom and Australia, each with 50-60 documents. Cluster analysis identified key themes such as mental health, psychological well-being, and athlete performance, along with emerging topics like community-based interventions and modern technological applications. This study offers a comprehensive overview of the literature trends in this field, emphasizing the importance of evidence-based, multidisciplinary strategies to effectively support athlete mental health and performance.